Manufacturing Martha’s Madness: Enslavement, Anxiety, and Distraction in Luke 10:38–42 - Henning, Meghan (Harvard theological review, 2025)
The story of Mary and Martha is a "text of terror" for women and the mentally disabled, elevating Martha as emblematic of the spiritual failure of the anxious woman. While scholarship has focused upon the precise nature of Martha’s work, this article argues that whether Martha was in the kitchen or doing ministry, she was doing servile labor and incurring the "slavish" worry associated with such work. Attention to the socio-economic context of Martha’s worry recenters the labor dispute that is at the heart of this short passage. Rather than naturalizing ancient norms about worry or continuing to use the disabled body as something to "think with," this article contextualizes Martha’s "worry and distraction," demonstrating the ties between the female body, worry, anxiety, and enslaved labor in antiquity. Martha’s worry is a disability that is manufactured by unjust labor structures that purposefully assign worry to some bodies and not others.